A mártírium toposza a Felvinczi Sándor halálára íródott prédikációkban és epigrammákban - Mikó, Gyula (Studia Litteraria, 2012)
Although Sándor Felvinczi, a Hungarian Calvinist preacher of Debrecen in the second half of seventeenth century was not persecuted by the Habsburgs or the Catholics, he was still represented as a martyr by funeral sermons and epigrams which were published to commemorate him in 1686 in a volume entitled Hedera Poetica. A few years after the decade of persecution (persecutio decennalis) most funeral texts used the topos of martyrdom. There are several Biblical and Classical sources of this early modern rhetorical tradition, and the present study sets out to examine these.